Dampak Pengembangan Daya Tarik Wisata Edukasi Dalam Peningkatan Pengunjung Perkampungan Budaya Betawi Setu Babakan - B. Syarifuddin Latif; Maya Amelia (Peneliti.net, 2022)
The Betawi tribe is an ethnic group in Indonesia whose residents generally occupy the DKI Jakarta area. DKI Jakarta has a cultural tourism destination that is famous for its unique Betawi culture, namely, Setu Babakan Betawi Cultural Village. The Setu Babakan Betawi Cultural Village has a variety of tourist attractions that can become an educational tourist destination by traveling while learning about Betawi culture. In addition, it is expected to have an impact on the development of educational tourism that should be preserved from the uniqueness of Betawi culture to visitors, especially students, as a form of educative cultural preservation in Setu Babakan Betawi Cultural Village. The purpose of this study is to evaluate the impact of developing an educational tourist attraction which is expected to increase visitors, especially students and students. Thus, students can recognize the educational uniqueness of Betawi culture, and can preserve Betawi culture in a sustainable manner now and in the future. The research method used is descriptive qualitative research method. The data taken is primary data using primary data collection techniques such as observation, interviews, and documentation conducted with the manager of the tourist destination of Setu Babakan Betawi Cultural Village.